Effects of Feed Deprivation on the Biochemical Responses of Pangasianodon hypophthalmus - Charan, K. S.; Nagesh, T.S.; Abraham, T.J.; Bhanu Prakash Ch; Das , Sarita, K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The effects of feed deprivation, including feed restriction and starvation, were investigated on the biochemical responses of Pangasianodon hypophthalmus over a 28-day period. Juvenile P. hypophthalmus were divided into three groups: control (daily feeding), feed limited (fed every third day) and deprived (no feeding). Blood samples were collected weekly. Results showed a significant decrease (P<0.05) in total protein and calcium levels in fish subjected to feed restriction and starvation. Although glucose levels decreased, the difference was not statistically significant (P>0.05). Cortisol levels in feed-deprived fish showed significant variations (P<0.05) with an erratic trend. Notably, lactate dehydrogenase (LDH) and creatinine levels exhibited significant increases (P<0.05). Throughout the starvation period, alanine transaminase (ALT) and aspartate transaminase (AST) levels rose, yet compared to the control, their concentrations did not significantly differ (P>0.05). The study concludes that total protein, LDH, and calcium, among other biochemical markers, were particularly sensitive to hunger-induced stress in P. hypophthalmus. This kind of study already conducted on some freshwater catfishes (Mustafa S., Tripathi G.) and catfiahes.